A science-based approach to guide Amur leopard recovery in China. (June 2017) - Wang, Tianming; Feng, Limin; Yang, Haitao; Han, Boyu; Zhao, Yiheng; Juan, Lin; Lü, Xinyue; Zou, Liang; Li, Tong; Xiao, Wenhong; Mou, Pu; Smith, James L.D.; et al.
Abstract: The future of the critically endangered Amur leopard ( Panthera pardus orientalis ) is at a crucial point, and effective conservation strategies implemented within its primary historical range in Northeast China may determine the fate of this species. However, when a conservation plan was first developed for the species, scarce information on the leopards' status existed. To illustrate regional conservation challenges, we focused on the Hunchun Nature Reserve and the surrounding area along the China-Russia border, a potential stronghold for Amur leopard conservation. We conducted large-scale data analysis with a field camera-trapping network to present the first population estimates for this species using a spatially explicit capture–recapture approach. We then used a zero-inflated regression model to analyze the relationship of leopards with major prey species and anthropogenic disturbances. Our results indicate that leopards are returning to China, but most of them are part of a "border population" or are transient; their numbers are far too few to establish a healthy population. The spatial counts of leopards were noticeably high in areas with high prey richness and areas far from settlements and roads. Areas with few prey species and high human and cattle use exhibited a greater probability of "excess absences" of leopards. Mitigating human disturbances by progressively minimizing cattle and human impacts on the forest should be pursued along with habitat expansion for large ungulates, whose presence is essential for leopard occupancy. This study provides crucial information to support Chinese government recovery efforts and for refining conservation practices in human-dominated landscapes to ensure the long-term survival of this species. Highlights: We assess Amur leopard status along the China–Russia border. Leopard is returning to China and begins to occupy inland areas from border. Reducing human disturbance and livestock grazing in forests should be pursued. Scientific management practices ensure a success of leopard conservation.